Self Care Prisoners At The Women's Penitentiary in Kendari - Ema Nengsyi; Diah Indriastuti; Fikki Prasetya; Tahiruddin Tahiruddin; Risqi Wahyu Susanti (KLASICS, 2022)
Abstract : The prisoner’s problem in correctional institutions is the restriction that affect psychological conditions. The disorder is further aggravated by not fulfilling human basic needs, such as love belonging need. However, inmates experience family seclusion. The purpose of this study is to explore the description of prisoners' self care in fulfilling love and belonging needs. This qualitative research involved as many as 6 people with a phenomenological approach. The research’s results consist of 3 themes namely problem, relatationship and adaptation. prisoners have different characteristics, so the ways to deal with problems and adapt are not the same. Self care deficit occurs because of a disconnected relationship between prisoners and their families, then added to the problems faced in prison and the process of adaptation that is not easy for some prisoners.